2022
DOI: 10.1371/journal.pone.0269241
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the use of prescription drugs and dietary supplements in obese respondents in the National Health and Nutrition Examination Survey

Abstract: Introduction Obesity is a common disease and a known risk factor for many other conditions such as hypertension, type 2 diabetes, and cancer. Treatment options for obesity include lifestyle changes, pharmacotherapy, and surgical interventions such as bariatric surgery. In this study, we examine the use of prescription drugs and dietary supplements by the individuals with obesity. Methods We conducted a cross-sectional analysis of the National Health and Nutrition Examination Survey (NHANES) data 2003–2018. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The epidemic of obesity is associated with a steady rise in drug consumption in order to treat several associated diseases such as type 2 diabetes mellitus (T2DM), hypertension, atherosclerosis, dyslipidemia and osteoarthritis [ 1 , 2 ]. In addition, numerous drugs are currently being developed in order to specifically treat nonalcoholic fatty liver disease (NAFLD), which is frequently associated with obesity and overweight [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The epidemic of obesity is associated with a steady rise in drug consumption in order to treat several associated diseases such as type 2 diabetes mellitus (T2DM), hypertension, atherosclerosis, dyslipidemia and osteoarthritis [ 1 , 2 ]. In addition, numerous drugs are currently being developed in order to specifically treat nonalcoholic fatty liver disease (NAFLD), which is frequently associated with obesity and overweight [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Use of HDSs has also been shown to be more prevalent among individuals with chronic medical conditions, including cardiovascular disorders, cancer, and obesity. 26,[40][41][42][43][44][45][46][47] In our study, we found diabetes, arthritis, and thyroid disorder independently associated with HDS use, but not cardiovascular disorder or cancer.…”
Section: Discussionmentioning
confidence: 77%